Burnout amongst school counselors: a study in a Chinese city - Chen, Wencheng (2021)
There is national and international research evidence that school counselors are prone to suffering burnout. Limited official data shows a similar situation in Ningbo in recent years. This research aims at exploring school counselors’ burnout in Ningbo.